A visual and organic vapor sensitive photonic crystal sensor consisting of polymer-infiltrated SiO2 inverse opal1. Issue 15 (21st April 2015) - Zhang, Yuqi; Qiu, Jianhua; Hu, Rongrong; Li, Pei; Gao, Loujun; Heng, Liping; Tang, Ben Zhong; Jiang, Lei
<x xml:space="preserve">Abstract</x> Tetraphenylethene polymer-infiltrated SiO2 inverse opal can detect tetrahydrofuran/acetones vapors according to the color change, which is resulted from the adsorption–desorption of vapors.